2008
DOI: 10.1109/icassp.2008.4518540
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized MMSE spectral magnitude estimation for the enhancement of noisy speech

Abstract: The enhancement of short-term spectra of noisy speech can be achieved by statistical estimation of the clean speech spectral components. We present a minimum mean-square error estimator of the clean speech spectral magnitude that uses both a parametric compression function in the estimation error criterion and a parametric prior distribution for the statistical model of the clean speech magnitude. The novel parametric estimator has many known magnitude estimators as a special solution and, additionally, afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 13 publications
0
91
0
Order By: Relevance
“…While there are many fidelity criteria it was recently found that the MMSE of the root spectral amplitude provides a good tradeoff between speech distortion, musical noise and noise reduction [8]. The corresponding fidelity criteria is given by…”
Section: Early Speech Component Estimatormentioning
confidence: 99%
“…While there are many fidelity criteria it was recently found that the MMSE of the root spectral amplitude provides a good tradeoff between speech distortion, musical noise and noise reduction [8]. The corresponding fidelity criteria is given by…”
Section: Early Speech Component Estimatormentioning
confidence: 99%
“…The constant parameters μ and γ can be tuned to yield several types of estimators. In [21], μ = 0.5 and γ = 0.5 have been identified as a good compromise between the amount of musical noise and the clarity of speech and are, therefore, also applied here. For obtaining the correct approximation for the selected values of μ and γ , the exponents p 0 and p ∞ in (16) have to be set to 0.5 and 1.0, respectively [42].…”
Section: Mmse Estimatormentioning
confidence: 99%
“…Here, the MMSE estimator described in [21] is used to obtain the clean speech magnitude, which requires the PSDs of the speech signal and the interference. It has been shown, e.g., in [3,18], that attenuating late reverberation is crucial for ASR while early reflections can be mitigated well by, e.g., cepstral mean subtraction (CMS) [35].…”
Section: Speech Enhancement (Se)mentioning
confidence: 99%
See 2 more Smart Citations